A kora újkori magyarországi imádság- és meditációirodalom kutatásának legújabb eredményei és tendenciái - Fazakas, Gergely Tamás (Studia Litteraria, 2013)
In my paper I provide a review of recent Hungarian research on early modern devotional literature. While the studying of sermons from the period between the fifteenth and eighteenth centuries has already been started in the Communist era, texts of prayers and meditations were not sufficiently examined, even though Zsuzsanna Erdélyi has published various crucial works on archaic Hungarian prayers since 1974. However, in the last few decades several Hungarian research projects, conferences, monographs, volumes of studies and text editions have been published, the historiographical reading of which is one of the main objectives of the present essay. I also wish to survey some foreign publications on these prayers and meditations which might encourage further Hungarian research.